2017
DOI: 10.1021/acs.biomac.7b00889
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Peptide-Carbon Nitride Hydrogel as a Light-Responsive Scaffold Material

Abstract: Peptide self-assembly is a facile route to the development of bioorganic hybrid materials that have sophisticated nanostructures toward diverse applications. Here, we report the synthesis of self-assembled peptide (Fmoc-diphenylalanine, Fmoc-FF)/graphitic carbon nitride (g-CN) hydrogels for light harvesting and biomimetic photosynthesis through noncovalent interactions between aromatic rings in Fmoc-FF nanofibers and tris-s-triazine in g-CN nanosheets. According to our analysis, the photocurrent density of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 35 publications
2
45
0
4
Order By: Relevance
“…Reversible assembly of g‐CN particles in water was shown to provide hydrogel‐like 3D networks, presenting dye absorption and degradation platforms . Recently, it was employed in polymer chemistry to perform photopolymerization or fabricate hydrogels . It was shown that g‐CN sheets act as reinforcer and photoinitiator in radical mediated hydrogel formation with surface charge being one of the important parameters regarding hydrogel strength .…”
Section: Methodsmentioning
confidence: 99%
“…Reversible assembly of g‐CN particles in water was shown to provide hydrogel‐like 3D networks, presenting dye absorption and degradation platforms . Recently, it was employed in polymer chemistry to perform photopolymerization or fabricate hydrogels . It was shown that g‐CN sheets act as reinforcer and photoinitiator in radical mediated hydrogel formation with surface charge being one of the important parameters regarding hydrogel strength .…”
Section: Methodsmentioning
confidence: 99%
“…[32] Quantenpunkte sind besonders photostabil und kçnnen mehrere Anregungszyklen durchlaufen. [34,35] Diese Materialien sind umweltverträglicher und weisen eine hçhere Biokompatibilitäta uf als klassische QDs,d ie giftige Schwermetalle wie Cadmium und Chalkogenide enthalten. Darüber hinaus lassen sich die photophysikalischen Absorptionseigenschaften von Quantenpunkten sowie deren Emissionsspektren und die Effiziens der durch Belichtung erzeugten Tr ennung von Ladungsträgern durch die Va riation ihrer Grçße und Zusammensetzung präzise einstellen.…”
Section: Grundlagenunclassified
“…In aktuellen Arbeiten wurden auch kohlenstoffbasierte Nanomaterialien wie graphitisches Kohlenstoffnitrid (g-C 3 N 4 )und C-Dots (CDs) in photobiokatalytischen Anwendungen eingesetzt. [34,35] Diese Materialien sind umweltverträglicher und weisen eine hçhere Biokompatibilitäta uf als klassische QDs,d ie giftige Schwermetalle wie Cadmium und Chalkogenide enthalten. [36] g-C 3 N 4 ist ein metallfreier polymerer Photokatalysator mit starker Absorption im Bereich sichtbaren Lichts und einer Bandlücke von etwa 2.7 eV.…”
Section: Grundlagenunclassified
See 2 more Smart Citations